Thirst of steel [large type] - Kendig, Ronie (Kendig, Ronie. Tox files, 2018)
"Cole 'Tox' Russell only wants to begin his life with Haven Cortes, but he and his team must first complete a final mission: retrieve the sword of Goliath and destroy the deadly Arrow & Flame Order"--